P675 ECHO COLOR DOPPLER EVALUATION OF SPLANCHNIC HEMODYNAMIC DURING ACUTE HEART FAILURE. (17th January 2020) - Ricco", B; Sacchi, A; Galassi, A; Messora, R; Bertolotti, M; Pinelli, G; Turrini, F
Abstract: BACKGROUND: Acute heart failure (AHF) seems to provoke profound derangement of abdominal hemodynamic, which causes symptoms and impacts on renal function. METHODS: 27 patients (10 F - age 78 - EF 0.39) admitted for AHF underwent cardiac and abdominal ultrasound at day 1 and 5. Arterial and venous flow within liver, spleen and kidney were recorded. Portal and Splenic Vein flow was described as continuous, pulsatile or reversed, whereas hepatic vein systolic and diastolic ratio was measured. Renal Venous Doppler Profile (VDP) was classified as: continuous, pulsatile, biphasic or monophasic. Arterial Resistive Index (RI) ≥0.7 was considered elevated. OUTCOME: At day 1 most patients presented with some degree of deranged VDP and high RI in all examined organs. At day 5, a significant proportion of patients improved their VDP in Liver, Kidney and Spleen, while the percentage of patients with collapsing IVC did not significantly change. On the arterial side, the proportion of patients with high Hepatic RI dropped significantly. CONCLUSIONS: Our preliminary data show that most deranged VDP in abdominal organs and Hepatic RI improve after decongestion despite a nonsignificant trend in improvement in IVC profile.